Analisis Kepuasan Mahasiswa Terkait Kinerja Pembelajaran Daring oleh Dosen Via Aplikasi Whatsapp Grup - Mohammad Auza’i Aqip; Muslimin (Indonesian Journal of Humanities and Social Sciences, 2020)
Distance learning is an alternative to learning in the Covid19 era by using the Whastapp Group application. Where the educator plays a major role, namely the lecturer. Lecturers who are given the mandate to guide students must have specific skills, including pedagogical competence, professional competence, personality competence, and social competence. Learning by lecturers is like services provided to consumers or college students. In providing services, of course, what must be considered is the quality of the service itself. The level of service quality can only be seen by consumers or college students. When the quality of service exceeds the expectations thought by college students, a sense of satisfaction will arise. The description of student satisfaction related to distance learning performance by lecturers is very satisfying for all indicators of personality and social competence.